Exploring students’ attitudes towards English as Lingua Franca: A case of UPIISM awardees (Passage: Journal of English Language and Literature, 2025)
In an increasingly globalized academic landscape, English as a Lingua Franca (ELF) has become an essential tool for communication among speakers from diverse linguistic and cultural backgrounds. This study explores the language attitudes of Indonesian university students, UPIISM awardees participating in an international exchange program, toward ELF in academic and social settings. Drawing on Garrett’s (2010) tripartite model of language attitudes, the study examines three components: cognitive (beliefs and perceptions), affective (emotions and feelings), and behavioral (actions and strategies). Using a qualitative design with purposive sampling, data were gathered from 14 UPIISM awardees through Likert-scale questionnaires and semi-structured interviews. Findings reveal that the awardees held strongly positive cognitive and behavioral attitudes toward ELF, recognizing its role as a practical, inclusive means of communication. Affective responses, however, varied, reflecting challenges such as anxiety and fear of judgment in intercultural interactions. Despite these concerns, they demonstrated a high degree of adaptability through rephrasing, gesturing, and pragmatic problem-solving strategies. Overall, the study underscores ELF’s role in fostering intercultural competence while highlighting the lingering influence of native-speaker ideologies. It calls for ELF-aware pedagogy and intercultural communication training to enhance student readiness for global engagement, and contributes to ongoing discussions on the role of English in international education, particularly within Southeast Asian contexts.